Contemporary Central American fiction : gender, subjectivity and affect - Browitt, Jeff (Sussex Academic Press, 2018)
"This book is a series of original, critical meditations on short stories and novels from Central America between 1995 and 2016. During the Cold War, literary art in Central America, as in Latin America in general, was strongly over-determined by the politics of the Cold War, which gave rise to popular struggle and three major armed civil wars in the 1970s and 1980s in Nicaragua, El Salvador and Guatemala. The period produced intense literary activity with political ideology central, personified by social denunciation in the testimonial novel and revolutionary poetry. Since then, though themes of violence are still at much of its core, Central American fiction has become more complex. We have witnessed a resurgence of literary writing and criticism with a focus squarely on the artistic side of narrative art: writing aware of its own figurative manoeuvres and inventiveness, its philosophical and affective dimensions, and its carefully crafted syntax. This collection of essays by Jeffrey Browitt attempts to trace some of the contours of this new literature and the contemporary subjectivities of its writers through close readings of Guatemala's Rodrigo Rey Rosa, Eduardo Halfon and Denise Phé-Funchal; Nicaragua's Franz Galich and Sergio Ramírez; Belize's David Ruiz Puga; El Salvador's Jacinta Escudos and Claudia Hernández; and Costa Rica's Carlos Cortés. Key themes are gender, subjectivity and affect as these intersect with the deconstruction of the family, hegemonic masculinity, motherhood, revolutionary romanticism, and the relationship of humans with animals"-- Provided by publisher.
"First published in 2018 in Great Britain by SUSSEX ACADEMIC PRESS PO Box 2950 Brighton BN2 5SP and in the United States of America by SUSSEX ACADEMIC PRESS International Specialized Book Services"--Title page verso
Keywords: Central American fiction -- 20th century -- History and criticism.; Central American fiction -- 21st century -- History and criticism.; Families in literature.; Sex role in literature.; Subjectivity in literature.; Reality in literature.; Affect (Psychology) in literature.; Human-animal relationships in literature.; Roman centraméricain -- 20e siècle -- Histoire et critique.; Roman centraméricain -- 21e siècle -- Histoire et critique.; Familles dans la littérature.; Rôle selon le sexe dans la littérature.; Subjectivité dans la littérature.; Réalité dans la littérature.; Relations humain-animal dans la littérature.; LITERARY CRITICISM -- Caribbean & Latin American.; Affect (Psychology) in literature; Central American fiction; Families in literature; Human-animal relationships in literature; Reality in literature; Sex role in literature; Subjectivity in literature; 1900-2099; Criticism, interpretation, etc.